PENGARUH PENGETAHUAN, RISIKO, PROMOSI TERHADAP MINAT BERINVESTASI REKSA DANA BAGI GENERASI Z DI KOTA JAMBI - Siti Asni Nasution; Efni Anita; Ogi Saputra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research results show that investment knowledge (X1) does not have a significant effect on investment interest (Y). This is proven by carrying out a statistical test which produces a significant Tcount value of 0.484 < Ttable 1.661 and a sig value of 0.630 > 0.50, which means that H0 is accepted and Ha is rejected. Investment risk (X2) shows that there is a significant influence on investment interest (Y). This can be proven by a Tcount value of 2.988 > Ttable 1.661 and a sig value of 0.004 > 0.50, which means that H0 is rejected and Ha is accepted. Investment promotion (X3) shows that there is a significant influence on investment interest (Y). This can be proven by a Tcount value of 4.538 > Ttable 1.661 and a sig value of 0.001 > 0.50, which means that H0 is rejected and Ha is accepted. Investment knowledge, investment risk and investment promotion together have a significant effect on investment interest. This is known by the significant values for (X1), (X2) and (X3) which simultaneously have an effect on (Y) of 0.001 < 0.05 and the value of fcount > ftable (34.090 > 2.700). The coefficient of determination shows that the influence of the independent variables (X1), (X2) and (X3) on (Y) has an influence of 50.1% and the remaining 49.9% is influenced by other variables outside of those that were not carefully studied in this research. So it can be concluded that there is one variable (X1) where Ha is rejected and H0 is accepted and 2 variables (X2), (X3) where Ha is accepted and H0 is rejected. This means that the higher the knowledge, the risk taken will not affect interest in investing